Gallbladder carcinoma: causes of misdiagnosis at CT. Issue 1 (January 2016) - Kim, S.W.; Kim, H.C.; Yang, D.M.; Ryu, J.K.; Won, K.Y.
Abstract : Gallbladder carcinomas can present with varied imaging features on computed tomography. The three major imaging features include (1) focal or diffuse wall thickening with or without irregularity of the gallbladder; (2) polypoidal intraluminal mass; and (3) large mass obscuring and replacing the gallbladder, often extending to the liver. Patterns of wall thickening or polypoid growth are often confused with various benign gallbladder diseases due to overlap of imaging findings. Moreover, gallbladder carcinomas that coexist with benign gallbladder diseases make accurate preoperative diagnosis more difficult. Recently, high-resolution ultrasound (HRUS) has been regarded as a problem-solving tool for gallbladder diseases. In this article, we will illustrate various imaging presentations of gallbladder cancer, along with imaging pitfalls and recently updated HRUS findings.